Ból kręgosłupa szyjnego w przebiegu radikulopatii = The cervical spine pain in radiculopathy - Litak, Jakub; Grochowski, Cezary; Kulesza, Bartomiej; Kamieniak, Piotr (Journal of Education, Health and Sport, 2017)
Litak Jakub, Grochowski Cezary, Kulesza Bartłomiej, Kamieniak Piotr. Ból kręgosłupa szyjnego w przebiegu radikulopatii = The cervical spine pain in radiculopathy. Journal of Education, Health and Sport. 2016;6(11):500-510. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.189567 http://ojs.ukw.edu.pl/index.php/johs/article/view/4025 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. Ból kręgosłupa szyjnego w przebiegu radikulopatii Jakub Litak¹, Cezary Grochowski², Bartłomiej Kulesza¹, Piotr Kamieniak¹ ¹Oddział Neurochirurgii i Neurochirurgii Dziecięcej SPSK-4 w Lublinie ²Katedra i Zakład Anatomii Prawidłowej Człowieka Uniwersytetu Medycznego w Lublinie The cervical spine pain in radiculopathy Jakub Litak¹, Cezary Grochowski², Bartłomiej Kulesza¹, Piotr Kamieniak¹ ¹Department of Neurosurgery and Pediatric Neurosurgery SPSK-4 in Lublin ²Department of Human Anatomy Medical University of Lublin Key words: cervical discopathy, radiculopathy, neck pain Abstrakt Bóle kręgosłupa szyjnego stanowią poważny problem diagnostyczny w praktyce lekarskiej . Są najczęstszą przyczyną zgłaszania się do lekarza i mają znaczący wymiar ekonomiczny. W związku z rozwojem cywilizacyjnym, stresem , siedzącym trybem życia i ograniczeniem aktywności procesy degeneracyjno - wytwórcze w kręgosłupie szyjnym stają się bardziej powszechne. Radikulopatia szyjna jest neurologicznym stanem wywołanym kompresją lub uszkodzeniem korzeni nerwowych szyjnego odcinka kręgosłupa. Stan ten generuje ból w obrębie szyi nie rzadko promieniuje do obręczy barkowej i kończyn górnych. Postępowanie diagnostyczne jest procesem wieloetapowym. Wywiad i badanie fizykalne pełnia znaczącą rolę a badania obrazowe uzupełniają pełną diagnozę. Farmakoterapia i ograniczenie obciążeń redukują ból w ostrej fazie. W przypadku nieskuteczności leczenia zachowawczego , przewlekłego bólu czy tez postępujących deficytów neurologicznych przeprowadzenie zabiegu operacyjnego obarczającego uciśnięte struktury nerwowe staje się jedynym słusznym postępowaniem . Słowa kluczowe: szyjna dyskopatia, radikulopatia, ból kręgosłupa szyjnego Abstract The cervical spine pain represents serious diagnostic medical problem .It is the most common reason for visiting the doctor and has economic dimension . According to Development of Civilization , stress , sitting lifestyle and limitation of physical activity Degenerative and Osteoarthritic syndromes become more common. Cervical radiculopathy is a neurological condition caused by compression or damage of the nerve roots of the cervical spine. This leads to the occurrence of the neck pain radiating to the shoulders and upper extremities. Diagnostic path is a multistage process. Medical interview and physical examination perform essential role . Imaging tools complete proper diagnosis . Pharmacotherapy and short term immobilization reduce pain in a acute phase of disease . However when conservative treatment fails and the patient reports chronic pain, progressive neurological deficits appears , surgery may be considered in order to decompress constricted neurological structures, as a best relieving pain treatment . Key words: cervical discopathy, radiculopathy, neck pain